2018
DOI: 10.3892/etm.2018.6643
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of IL-15 and IL-17 in synovial fluid of rheumatoid arthritis animal model

Abstract: The aim of the present study was to investigate the expression levels of interleukin-15 (IL-15) and interleukin-17 (IL-17) in synovial fluid of rheumatoid arthritis (RA) animal model, and to investigate their correlations with RA. A total of 100 Wistar rats were selected, among which 60 rats were used to establish the collagen II-induced arthritis (CIA) model as the model observation group, and the remaining 40 rats were used as blank control group. The levels of IL-15 and IL-17 in synovial fluid were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…Higher serum IL-15 levels in RA patients which may contribute to the observed NK cell increase. Jin et al who showed that the level of IL-15 and IL-17 were significantly elevated in synovial fluid of rats and involved in the perpetuation of RA synovitis 13 www.nature.com/scientificreports www.nature.com/scientificreports/ NKp46, a natural cytotoxicity receptor, mediates NK cell-induced cell lysis and provide an innate defense against intracellular pathogens, NKp46 also serve as a key factor in the pathogenesis of type 1 diabetes mellitus by recognition of pancreatic β cells ligands [15][16][17] . We observed NK cells from RA patients expressed lower NKp46 than those from controls, and IL-15 decreased NKp46 expression of NK cells from RA patients, similar to that observed in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum IL-15 levels in RA patients which may contribute to the observed NK cell increase. Jin et al who showed that the level of IL-15 and IL-17 were significantly elevated in synovial fluid of rats and involved in the perpetuation of RA synovitis 13 www.nature.com/scientificreports www.nature.com/scientificreports/ NKp46, a natural cytotoxicity receptor, mediates NK cell-induced cell lysis and provide an innate defense against intracellular pathogens, NKp46 also serve as a key factor in the pathogenesis of type 1 diabetes mellitus by recognition of pancreatic β cells ligands [15][16][17] . We observed NK cells from RA patients expressed lower NKp46 than those from controls, and IL-15 decreased NKp46 expression of NK cells from RA patients, similar to that observed in controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, around 50% are unresponsive to treatment as well as biologics targeting these cytokines increase the incidence of infection (8,32). IL-15 contributes to RA physiopathology by stimulating T-cell development and survival, delaying the apoptosis of fibroblast-like synoviocytes as well as by recruiting neutrophils and lymphocytes to the inflammatory foci (17,33,34). A phase I-II clinical trial using a human IgG1 monoclonal antibody to target IL-15 reduced the disease activity according to the American College of Rheumatology criteria by 20% (ACR20) in 63% of patients, ACR50 in 38% of patients, and ACR70 in 25% of patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is one of the most important regulators of innate and adaptive immune responses, and it is expressed in synovial tissues, and could contribute to cartilage degeneration and synovial infiltration in joint by inducing the release of chemokines by chondrocytes [29,30]. Furthermore, studies in animal models suggest that IL-17 knock-out mice contribute to more severe RA than wild-type animals [31]. We have reasons to believe that IL-17 may contribute to the development of knee OA.…”
Section: Discussionmentioning
confidence: 99%